Professional Athletes Maintain High TNF-Alpha or IFN-Gamma Related Inflammatory Status after Recovering from COVID-19 Infection without Developing a Neutralizing Antibody Response - Mira Ambrus; Eszter Fodor; Timea Berki; Veronika Müller; Ádám Uhlár; István Hornyák; Zsombor Lacza (Sports, 2023)
Introduction: Professional athletes are endangered by COVID-19 and belong to the high-risk population due to their lifestyle. To obtain information on the behavior of COVID-19 in professional athletes, serological, cytokine, and virus neutralization capacities were analyzed. Materials and methods: Hungarian national teams participated in international sports events during the early phases of the COVID-19 epidemic in 2020. Altogether, 29 professional athletes volunteered to donate plasma. Their serological status was evaluated by IgA, IgM, and IgG ELISAs and the highest virus neutralization titer in an in vitro live tissue assay. Plasma cytokine patterns were analyzed with a Bioplex multiplex ELISA system. Results: Surprisingly, only one athlete (3%) had anti-SARS-CoV-2 IgG, while IgA was more common (31%). Neither plasma showed direct virus neutralization in a titer over 1:10; hence, they were not suitable for reconvalescent treatment. The ‘cytokine storm’ markers IL-6 and IL-8 were at baseline levels. In contrast, either the TNF-alpha-related cytokines or the IFN-gamma-associated cytokines were elevated. There was a strong negative correlation between the TNF-alpha- or IFN-gamma-related cytokines. Conclusions: Professional athletes are susceptible to the SARS-CoV-2 infection without developing long-term immunity through neutralizing immunoglobulins. Elevated secretory and cellular immunity markers indicate that these systems are probably responsible for virus elimination in this subpopulation.